Literature Review in International Trade Forecasting Based in Machine Learning Method - Tong Ye (SHS Web of Conferences, 2023)
In recent years, with the intricacy of international politics and economic situation and the anti-globalization trend, China’s trade with world is facing many serious challenges. There are more factors that effects China export and import. Because of that, high-precision forecasting for international trade is beneficial for nation’s government, guild and export and import enterprise that need a judgement or decision for future. To better promote future research, the paper reviews the paper written by experts from world in trade forecasting field, classifies and summarizes their opinion according in their adopting machine learning method.